The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4236/ojog.2018.812118
|View full text |Cite
|
Sign up to set email alerts
|

Mother to Child Transmission of HIV after Option B+ in Low Income Environment

Abstract: Background: In Cameroon, the prevalence of HIV in pregnant women was 7.8% in 2012, and they were 8500 HIV positive newborns in 2013. Option B+ is the first highly active antiretroviral therapy (HAART) preventive protocol. The objective was to evaluate the rate of HIV transmission on children born from mothers who were on Option B+ during pregnancy, in three university teaching hospitals of the University of Yaoundé I. Methods: It was a retrospective, cross-sectional study over a period of four years (2013-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Data collected for this review were summarised in Table 2, which identified 22 studies from 11 African Countries that met inclusion criteria (Cameroon, Ethiopia, Lesotho, Malawi, Rwanda, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe). Study designs varied as follows: there were 13 retrospective cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] ; five prospective cohort studies [37][38][39][40]45 ; two cross-sectional studies 41,42 and one randomised control trial (RCT). 43 Sample sizes ranged from 124 13,15 to 2505 women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data collected for this review were summarised in Table 2, which identified 22 studies from 11 African Countries that met inclusion criteria (Cameroon, Ethiopia, Lesotho, Malawi, Rwanda, South Africa, Swaziland, Tanzania, Uganda, Zambia and Zimbabwe). Study designs varied as follows: there were 13 retrospective cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] ; five prospective cohort studies [37][38][39][40]45 ; two cross-sectional studies 41,42 and one randomised control trial (RCT). 43 Sample sizes ranged from 124 13,15 to 2505 women.…”
Section: Resultsmentioning
confidence: 99%
“…26 More commonly, infant HIV status was determined at an older age or whenever the infant was brought to the clinic. Loss to follow-up (LTFU) was addressed in only 14 of the 22 studies and varied from 3% 24 to 47%. 37 Studies were carried out in many settings ranging from urban hospitals and clinics (13 studies) to rural clinics (3 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Zimbabwe reported an 18-month MTCT final outcome of 0.3% among a nationally-representative sample of 6,051 HEI [ 22 ], which was approximately 10 times lower than we found in our Nigerian cohort. However, there is wide variation across the continent; non-population-based studies from other African countries have reported post-breastfeeding/final outcome HIV positivity rates ranging from 2.2% to 9.6% for cohorts with approximately 170 to 3,780 HEI [ 23 – 27 ].…”
Section: Discussionmentioning
confidence: 99%